A wrinkled nanosurface causes accelerated protein unfolding revealing its critical role in nanotoxicity. Issue 48 (31st October 2022) - Li, Yuezheng; Li, Baoyu; Liu, Yang; Qu, Yuanyuan; Tian, Jian; Li, Weifeng
Abstract : Wrinkled nanosurface can cause more severe protein distorsions than planar nanosurface because of stronger interactions. Abstract : Wrinkles are often found to have a strong influence on the properties of nanomaterials and have attracted extensive research interest. However, the consequences of the use of wrinkled nanomaterials in biological systems remain largely unknown. Here, using molecular dynamics simulations, we studied the interactions of a wrinkled graphene with proteins, using the villin headpiece (HP35) as the representative model. Our results clearly revealed that the wrinkle, especially the wrinkle corner, showed stronger binding affinity to HP35 than the planar surface where HP35 experienced accelerated and more severe unfolding. This is because the transverse translocation of the aromatic residues of the protein is highly confined at the wrinkle corner. The movement of other parts of the protein causes unfolding of the protein secondary structure and releases hydrophobic residues to bind to graphene, causing complete denaturation. Further free energy analyses revealed that this is attributed to the stronger binding affinity of residues to the wrinkle corner than to the planar surface. The present findings provide a deeper understanding of the effect of graphene wrinkles on protein stability. This finding may be generalized to other types of biomolecules and may also guide the design of biomedical nanomaterials through surface structural engineering.